Juvenile Idiopathic Arthritis is Associated With Early Medical and Surgical Complications Following Primary Total Hip Arthroplasty: A National Database Study - Sean B. Sequeira, MD; Brian P. McCormick, MD; Mark D. Hasenauer, MD; Robert McKinstry, MD; Frank Ebert, MD; Henry R. Boucher, MD (Arthroplasty Today, 2024)
Background: Juvenile idiopathic arthritis (JIA) is an inflammatory arthropathy that classically affects children but can cause long-term deformity to the femoral head and hip joint, which may require an arthroplasty procedure. There is a paucity of data surrounding the medical and surgical outcomes of total hip arthroplasty (THA) in patients with JIA compared to a control cohort. Methods: Patients with JIA who underwent THA from 2010 to 2019 were identified in a large national insurance database. A propensity score matching algorithm was used to obtain a control cohort who did not have JIA based upon age, sex, and Elixhauser Comorbidity Index in a 1:10 ratio. Seven hundred sixty-three patients with JIA and 7434 patients without JIA were identified who underwent THA. Ninety-day medical outcomes, 1-year surgical outcomes, and 90-day return to the emergency department and readmission were calculated. Results: Patients with JIA were at increased risk of 90-day transfusion (odds ratio [OR] 1.79; P < .001), pneumonia (OR 2.68; P < .001), urinary tract infection (OR 2.64; P < .001), and wound disruption (OR 2.72; P < .001), as well as 1-year risk of revision THA (OR 2.27; P < .001), periprosthetic joint infection (OR 2.98; P < .001), periprosthetic fracture (OR 2.93; P < .001), aseptic loosening (OR 3.92; P < .001), dislocation (OR 2.61; P = .001), and debridement, antibiotics, and implant retention procedure (OR 2.71; P < .001). Patients with JIA were also at increased risk of 90-day emergency department visit (OR 2.54; P < .001) and readmission (OR 2.59; P < .001). Conclusions: Patients with JIA were at increased risk of early medical and surgical complications following THA. These findings are imperative for surgeons to consider and may warrant tailored perioperative decision-making to avoid the aforementioned medical and surgical complications.